Adolescent Fertility, Economic Development and Gender Parity in Asian Countries - Palanca-Tan, Rosalina (Archīum Ateneo, 2017)
Teenage pregnancy is an important problem within the area of general fertility and population growth. According to the World Health Organization (WHO), about 16 million women aged 15- 19 become pregnant each year. Teenage pregnancies constitute 11% of pregnancies worldwide, and 95% of teenage pregnancies happen in low- and middle-income countries (Mangiaterra et al. 2008). Using Becker’s framework, this paper aims to identify the factors that contribute to adolescent fertility across 34 Asian countries. Consistent with much of the theoretical and empirical literature, this study finds that higher labour productivity and stable prices (lower inflation rate) are associated with a lower incidence of adolescent fertility. Further, although the presence or absence of subsidies for child rearing does not impact significantly on adolescent fertility, the provision of educational opportunities specifically targeting the young female segment of the population appears to be a potent policy instrument.